An experimental and numerical study for cutaneous cryotherapy - Kumari C.; Kumar A.; Sarangi S.K.; Thirugnanam A. (My University, 2025)
The present study deals with an experimental and numerical study to quantify the skin necrosis during cryotherapy. Agarose gel (0.6% (w/v)) is used to mimic the thermal properties of the dermis. The spray cooling is performed with 0.8 mm, 0.6 mm and 0.4 mm nozzle diameters for a single freeze-thaw cycle of 120 s freezing and 130 s thawing. The distance from the nozzle to the gel surface (z) is maintained at 9 mm, 18 mm and 27 mm. The numerical modelling for the thermal analysis has been performed with enthalpy equation; the numerical results are well matched with the experimental results. The numerical results are used to calculate the lethal front, ablation volume and gap (distance between lethal and ice front) in the gel. The ablation volume obtained with 0.8 mm nozzle diameter for − 50oC and − 25oC isothermal surfaces is 83% and 62% smaller than the ice volume respectively for all the spraying distance. Similarly, it is 93% and 78% smaller for z = 27 mm while it is 91% and 73 ± 2% respectively for z = 18 mm and 9 mm in the case of 0.6 mm nozzle diameter. The present numerical model may help in the computerised planning of cryotherapy. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.